Modern education trends and value meanings of teacher educati - Korchinskiy А.А., Blokhin A.L., Boldinova O.G., Borzilov Y.P, Gshiyants R.E., (Opción, 1970)
This article presents analytical data on emerging or educational trends and an attempt to determine the value meanings of teacher education. Revealing the content of the article, the authors determine the main educational trends that affect the content of a modern teacher professional activities, which are classified by the authors into groups. The value meaning of modern pedagogical education is substantiated - the formation of a future bioethical culture among future teachers and their preparation for the translation of this culture into society and into the educational system